Pengaruh Poliherbal Ekstrak Jeringau, Temu Mangga Dan Bawang Putih Pada Fungsi Hepar Tikus (Rattus norwegicus) - Bayyinatul Muchtaromah; Rahmi Annisa; Sofiya Sofiya (INSTITUT AGAMA ISLAM NEGERI AMBON, 2019)
This study aims to determine the effect of polyherbal extract of jeringau (Acorus calamus), temu mangga (Curcuma mangga), and garlic (Allium sativum) on the levels of Glutamate Oxaloacetate Transaminase (GOT) and Glutamate Pyruvate Transaminase (GPT) enzymes in rat hepar. The results of this study can be used as an indicator of the safety of using natural-based drugs on the body. This study used a completely randomized design (CRD) with 9 treatments and 3 replications. Treatment consists of K- (without treatment), K + (clomiphene citrate dose of 0.9 mg/kg BW), P1 (combination 1 at dose 50 mg/kgBB, P2 (combination 1 at a dose of 75 mg/kgBB), P3 (combination 1 at a dose of 100 mg/kgBB, P4 (combination 2 at a dose of 50 mg/kgBB), P5 (combination 2 at a dose of 75 mg/kgBB), P6 (combination 2 at a dose of 100 mg/kgBB), P7 (Subur kandungan herb at dose of 75 mg/kgBB). The results showed the highest levels of GPT enzymes were found in the treatment group 3 with the administration of combination 1 extract with a dose of 100 mg / kg BW of 46.7 U/L and the lowest level at P7 14.4 U / L, while the highest GOT enzyme levels were found in P6 namely 57.6 U / L and the lowest at P4 23.3 U / L. The results of the levels of the two transaminase enzymes are still in the normal category. Keywords: Jeringau, Temu Mangga, Garlic, Hepar, GPT, GOT